(untitled) (PETITUM, 2023)
ABSTRACT: Research aims to find out law on customary land registration and procedures for customary land registration in Takalar Regency. Research method used descriptive method to describe systematically, factually and accurately data obtained using quantitative and qualitative analysis with interview techniques and filling out questionnaires. Research results show customary land registration in Takalar Regency has generally been carried out based on Basic Agrarian Law and PP No. 24 of 1997 concerning land registration, although at application level there are differences between mediator judges, they are only technical in nature, and customary land implementation with state land. It is recommended that there be special outreach and training for the community and authorized officials regarding registration procedures for customary and state land in Takalar Regency. Likewise, community’s legal knowledge and awareness about meaning and registering customary land importance at BPN in order to provide legal certainty to the community regarding their land. ABSTRAK: Penelitian bertujuan mengetahui hukum Pendaftaran tanah adat dan bagaimana Prosedur pendaftaran tanah adat di Kabupaten Takalar. Metode yang digunakan penelitian ini adalah metode deskriptif mendeskripsikan secara sistematis, faktual dan akurat terhadap data yang diperoleh dengan menggunakan analisis kuantitatif dan kualitatif dengan teknik wawancara dan mengisi kuisioner kepada pada responden. Hasil penelitian menunjukkan pelaksanaan pendaftaran tanah adat di Kabupaten Takalar secara umum telah terlaksana berdasarkan Undang – Undang Pokok Agraria dan PP No. 24 Tahun 1997 Tentang pendaftaran tanah, meskipun dalam tataran aplikasinya masih terdapat perbedaan diantara hakim mediator, namun hanya bersifat teknis, dan pelaksanaan Tanah adat dengan tanah negara tersebut. Disarankan perlu adanya sosialisasi dan pelatihan khusus bagi masyarakat dan pejabat yang berwenang mengenai prosedur pendaftaran tanah adat dan tanah negara di Kabupaten Takalar. Demikian pula pengetahuan dan kesadaran hukum masyarakat tentang makna dan pentingnya pendaftaran tanah adat di BPN guna memberikan kepastian hukum kepada masyarakat mengenai tanah mereka